Characterization and purification of wastewater sludge from rubber industry for value-added application - Tan, Xuan Ler (2024)
Rubber industries in Malaysia generate substantial volume of wastewater, ranging from 50 to 55 thousand m3 during raw rubber production and 100 to 130 thousand m3 daily for its derivatives manufacturing. Treating this wastewater has generated 240 tons of sludge annually. Due to the ineffective sludge management plan, the sludge is underutilized. A novel process that converts this sludge into valuable compound, while minimizing final waste would be a promising solution in the treatment of sludge. The composition of sludge from the rubber industry is highly complex due to various chemicals introduced during the manufacturing process, posing challenges to treatment. In this study, various characterization methods, including FTIR, SEM-EDX, XRD and TGA were conducted to provide insights into sludge properties. Along with that, Ca and Al were found to be the major components. Subsequently, an Aqua Regia digestion method was employed to determine the total metal concentration within the sludge. The concentration of Ca was found to be 71.88 mg/g of sludge, whereas the concentration of Al was found to be 47.47 mg/g of sludge. To treat the sludge and extract these prominent metals, acid leaching was selected as the treatment method. The leaching efficiency was investigated by adjusting its parameters: acid selection (H2SO4, HNO3, HCl), molar concentration of the acid (0.3, 0.5 and 1.0 M), liquid-tosolid ratio (3:1, 5:1 and 10:1), temperature (30, 50, 70 and 90 ℃), as well as duration (30, 60, 90 and 120 minutes). In this context, using 1.0 M HNO3 at a liquid-to-solid ratio of 10:1, under 90 ℃ for 90 minutes were determined as the optimum conditions for the acid leaching treatment process for the rubber sludge. The Al extraction efficiency achieved 100 %, while Ca reached 95.21 %. Further analysis of the post-leached residues indicated their potential for reuse as low-cost adsorbents, soil conditioners or energy sources. Not only that, but the Al and Ca in leachate could be recovered and utilized in other applications.